Advocacy for Leaders: Crafting Richer Stories for Public Health. Issue 3 (May 2016) - Matthews, Gene; Burris, Scott; Ledford, Sue Lynn; Baker, Edward L.
Abstract : This article describes fresh approaches for providing better insight into the US social landscape and gives useful perspectives to create better messaging for new coalitions to improve public health.